A simple methodology for creating and applying replicable, photograph‐accurate coloration to 3D‐printed models for animal behavior studies. (1st October 2022) - Mesken, Jarrod; Beckmann, Christa; McDonald, Paul G.
Abstract: Researchers often use artificial models of animals to elicit and study behavior. Until recently, these models were typically handcrafted; however, 3D‐printing technology has been adopted by researchers looking to create accurate and consistent animal models from scans of living animals, taxidermies, or existing models. While 3D‐printing techniques create models with accurate and repeatable shape and size, applying coloration to these models is still typically achieved with traditional methods, such as painting by hand. These approaches can be time‐consuming and require high levels of artistic skill, creating a barrier to producing realistic models, especially when more than one model or standardized coloration is required. Here, we present a simple workflow to avoid these issues by creating a photograph‐accurate paper "skin" that can be glued onto 3D‐printed animal models to provide surface coloration. We have used this methodology to create avian models for several experiments, and found that it can create highly detailed and standardized models with minimal training and is independent of artistic skill. Additionally, this method allows the files needed to accurately recreate models to be shared digitally with other researchers, further enhancing repeatability in the field. Abstract : A subject (such as a taxidermic mount) is scanned with a camera or 3D‐scanner to create a digital model. The digital model is 3D‐printed to create a physical model, and the surface texture is printed to create paper cutouts that can be glued onto the 3D‐printed model to recreate coloration in an accurate manner. This approach allows models to be modified on factors such as size and color while maintaining otherwise standardized appearance, and models to be easily shared online.